Electronic Communication as aSustainable Development Tool in Rural Areas in Poland - Wiesław Michał MAZIARZ (Communications of International Proceedings, 2021)
Sustainable development is nowadays defined in a very broad manner as, in addition to seeking to preserve natural balance, it also takes into account problems associated with economic growth, care for equitable access to social and cultural civilisational achievements, eradication of poverty or achievement of basic living standards. Such definition of sustainable development requires: comprehensive activities in many areas (economic, social, natural, cultural), cooperation of entities and institutions operating on the international, national as well as local level, use of various tools to eliminate or reduce existing disparities. In Poland, the idea of sustainable development should be particularly related to rural areas, whose development level differs significantly from urban areas in economic, social and cultural terms. This disproportion is a source of frustration for rural areas residents, who experience inequality in the level of existence, significant civilisational delay and less favourable prospects for social and economic advancement. Changing this state of affairs is a time consuming and very costly process; therefore, it is necessary to consider measures that can relatively quickly reduce developmental inequalities affecting rural areas. A rational solution that meets the above condition is the use of electronic communication. The aim of the paper is to present the possibilities of using the means and services of electronic communication to influence sustainable development of rural areas. The considerations presented in the article may provoke a more detailed discussion on the subject.
Keywords: Sustainable Development; Rural Areas; Electronic Communication